2012
DOI: 10.7763/ijfcc.2012.v1.12
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Fiber Based Erbium Doped Amplifiers and Their Gain

Abstract: The paper is based on the numerical solution of Euler's method to deal with the initial value problems for Erbium doped fiber amplifiers'(EDFAs)rate equations, and their gain dependences are discussed. Simulation of the propagation of the signal and pump power versus the amplifier length has been done. Modifying the input pump power and input signal power has obtained the gain profile of the PCF based EDFAs. Fiber designs which allow us to have large gain are presented and demonstrated that the PCF based Erbiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In this case, the un pumped region of the fiber absorbs the signal thus, resulting loss in signal rather than gain in that section. Figure (4) shows the gain coefficient as a function of the input power for different values of fiber length. This figure shows that for fiber length L=10m the gain reaches a saturation level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the un pumped region of the fiber absorbs the signal thus, resulting loss in signal rather than gain in that section. Figure (4) shows the gain coefficient as a function of the input power for different values of fiber length. This figure shows that for fiber length L=10m the gain reaches a saturation level.…”
Section: Resultsmentioning
confidence: 99%
“…of CW fiber amplifier they showed that gain saturation by strong fundamental mode 2011 [3].Peiying Chen and etal in 2012 gives a numerical solution of Eulers method to deal with initial value problems for fiber amplifier rate equations and their gain dependence [4].…”
mentioning
confidence: 99%
“…AV Smith et al [9] provided a numerical demonstration of the population inversion saturation and stimulated thermal Rayleigh amplification associated with laser amplification of a large-mode fiber amplifier. Chen Peiying et al (2012) [10] suggested a numerical Euler method solution to the fiber optimizer's frequency equation's initial value problem. Because of the unique properties and possible advantages of active fibers, heavily doped phosphate fibers were used [11].…”
Section: Introductionmentioning
confidence: 99%
“…Figure(5): Gain vs. pump power at diff. ion concentration of (YDFA), L=10m, p=968nm, s=1022nm, a=2.5m.…”
mentioning
confidence: 99%